Peran Metode Diskusi dalam Mengembangkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran PAK - Elisabethangreiny Elisabethangreiny; Ordekoria Saragih (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
subject.Critical thinking skills of students in PAK subject. Discussion method is a method that teachers use with students to carry out a learning process through how teachers and students or students with each other exchange ideas. Through how teachers and students or students with each other exchange opinions and have their own arguments to achieve learning goals. Opinions and have their own arguments to achieve the specified learning objectives. That have been determined. This discussion method is also very instrumental to the students, where students can develop students' critical thinking skills. The students. This research uses a qualitative approach with method (library research). Study literature study is a method used to collect data that is in accordance with what will be researched through a collection of journals, apparatus, books, or other publications that can be used as a source of research, by describing and describing the data. Research, by describing and describing data based on the opinions of experts. Experts' opinions. Research with this library study will summarize information needed so that the problem or topic presented can be understood comprehensively. Presented can be understood comprehensively about the role of the discussion method in developing students' critical thinking skills in PAK subjects. The benefits of The benefit of this research is to add insight to the readers regarding the the importance of the role of discussion methods in developing students' critical thinking skills in students in PAK subject.